Stable Isotope-Assisted Plant Metabolomics: Investigation of Phenylalanine-Related Metabolic Response in Wheat Upon Treatment With the Fusarium Virulence Factor Deoxynivalenol - Doppler, Maria; Kluger, Bernhard; Bueschl, Christoph; Steiner, Barbara; Buerstmayr, Hermann; Lemmens, Marc; Krska, Rudolf; Adam, Gerhard; Schuhmacher, Rainer (Frontiers in Plant Science, 2019)
The major Fusarium mycotoxin deoxynivalenol (DON) is a virulence factor in wheat and has also been shown to induce defense responses in host plant tissue. In this study, global and tracer labeling with 13C were combined to annotate the overall metabolome of wheat ears and to evaluate the response of phenylalanine related pathways upon treatment with DON. At anthesis, ears of resistant and susceptible cultivars as well as two related near isogenic wheat lines (NILs) differing in the presence/absence of the major resistance QTL Fhb1 were infiltrated with 1 mg DON or water (control) and samples were collected 0, 12, 24, 48 and 96 hours after treatment (hat). A total of 172 Phe derived metabolites were detected with our untargeted approach employing 13C-labeled phenylalanine and subsequently annotated as flavonoids, lignans, coumarins, benzoic acid derivatives, hydroxycinnamic acid amides (HCAAs) as well as peptides. 96 hours after the DON treatment, up to 30% of the metabolites biosynthesized from Phe showed significantly increased levels compared to the control samples. Major metabolic changes included the formation of precursors of compounds implicated in cell wall reinforcement and presumed antifungal compounds. Additionally, also dipeptides, which presumably are products of proteolytic degradation of truncated proteins generated in the presence of the toxin, were significantly more abundant upon DON treatment. An in-depth comparison of the two NILs with correlation-clustering of time course profiles revealed some 70 DON responsive Phe derivatives. While several flavonoids had constitutively different abundance levels between the two NILs differing in resistance, other Phe-derived metabolites such as HCAAs and hydroxycinnamoyl quinates were affected differently in the two NILs after treatment with DON. Our results suggest a strong activation of the general phenylpropanoid pathway and that coumaroyl-CoA is mainly diverted towards HCAAs in the presence of Fhb1, whereas the metabolic route to monolignol(-conjugates), lignans and lignin seems to be favored in the absence of the Fhb1 resistance QTL.